Malaysia's Multimedia Super Corridor-leading Asia's information age - Multimedia Development Corporation (Kuala Lumpur: MDC)
Introduction of Malaysia's Multimedia Super Corridor on leading Asia's information age.
System requirements: PC 486DX-33 or higher; 8MB free RAM [16MB recommended]; 3MB free hard disk space; 640x480 SVGA DISPLAY, 256 color 8-bit sound card; double speed CD-ROM drive; Win 3.1, Win 3.11 or Win 95; MAC 68040 or faster processor, 8MB free RAM [16MB recommended]; 3MB free hard disk space; system 7.1 or faster; 640x480x256 color video display; double speed CD-ROM drive
Keywords: Multimedia Super Corridor